Meningkatkan interdependensi kolektif dari dampak perubahan iklim - Hadi, Cholichul (Kajian Psikologi dan Kesehatan Mental, 2024)
Purpose: This study seeks to reconceptualize climate anxiety not as an individual pathology, as often framed in Western models, but as a form of collective interdependence that mobilizes adaptive action in vulnerable communities. By focusing on flood-prone villages in Bangladesh, the research highlights the role of anxiety as a socially embedded mechanism for resilience. Research Methodology: A 12-month longitudinal ethnography was conducted, complemented by dynamic social network modeling. The analysis integrated two components: (1) community transmission of climate anxiety using SIENA models, and (2) behavioral cascades of pro-environmental actions mapped through network thresholds. Results: Findings reveal that climate anxiety functions as an adaptive social glue. Villagers with the highest centrality of climate anxiety initiated 3.5 times more collective adaptation measures (p < 0.001). Moreover, threshold effects emerged, with network saturation at 60% producing non-linear acceleration of community-wide adaptive behavior. Conclusions: Rather than being medicalized as distress, climate anxiety in vulnerable contexts operates as a driver of interdependent resilience. It provides motivational energy that binds communities, channeling affect into coordinated action rather than individual pathology. Limitations: The study is limited to flood-prone Bangladeshi villages, which constrains the generalizability of findings to other environmental and cultural settings. The reliance on ethnographic immersion also introduces interpretive subjectivity. Contribution: The research advances climate psychology by reframing collective anxiety as a catalyst for resilience, challenging Eurocentric individualist models, and offering a novel integration of ethnography with network-based simulation in the Global South.